Secession, Democracy & Human Rights - Reimers, Patrick (2019)
The United Nations (UN) officially declared "self-determination" as a right of all peoples. Although the United Nations Charter (1945) offers some guidelines for the application of this right, there are major challenges in its implementation in the case of secessionist tendencies. Faced with this situation, the economist Jörg Guido Hülsmann, in his essay Secession and the Production of Defense, discussed not only the argument that pure private production is always superior to public and compulsory schemes, but also the current process of secession which, should always be justified against violent and coercive behavior of governments against (part of) its population. Hülsmann's ideas are presented in the contrast of the latest secessionist movements in Catalonia and Scotland, and in combination with Hayek's concept of "spontaneous order." The separatist movementin Catalonia is also analyzed based on the ideas of political scientist Margaret Moore, who advocates three types of normative theories that can justify the right to secession.